Bi-directional Modulation of Electron Transfer and Capacitive Behavior in Sediment Microbial Fuel Cells by Hydrochar and Acetate - Marcelinus Christwardana; Yayuk Astuti; H. Hadiyanto; Achmad Yanuar Maulana; K. Khoirunnisa; Dilla Dayanti; Keisya Natania Nur A'intan (International Journal of Renewable Energy Development, 2026)
Marine sediment microbial fuel cells (MS-MFCs) provide a sustainable means of harvesting energy from benthic environments, yet their performance is often constrained by slow electron transfer and unstable power generation. To address these limitations, this study investigates the coupled kinetic and capacitive enhancement of MS-MFCs through co-modification with biomass-derived hydrochar (HC) and acetate as complementary electron-transfer and metabolic modulators. Four sediment compositions (0, 5, 10, and 15% v/v HC) were operated over 30 days under a 1 kΩ external load, with acetate introduced on Day 21. The apparent electron-transfer rate constant (Kₛ) increased from 1.77 s⁻¹ in the unamended control to 3.19 s⁻¹ and 3.49 s⁻¹ in the 10% and 15% HC systems, respectively. Maximum power densities reached 21.8–23.1 mW m⁻², approximately three orders of magnitude higher than the control. Mechanistically, HC provided a conductive and pseudocapacitive scaffold that facilitated microbe–electrode coupling, while acetate served as a readily metabolizable carbon source to accelerate microbial activity. Together, these effects established a synergistic link between kinetic enhancement and capacitive charge buffering, offering new insight into the design of robust, self-sustaining MS-MFCs for in-situ coastal energy recovery.